An application connecting the logistic service providers and E- retailers - V. V. G. Ravi Teja, Lakshmi Sai Chandra Maddi (International Journal of Advanced Science and Technology, 2020)
The accelerated growth in the online shopping sector has challenged physical distribution service quality that is provided by retailers who are multichannel, pure players and logistics service providers. A consumer survey based on electronic physical distribution service quality resulted in identification of various issues which is the motivation for this research. It involved qualitative interviews with retailers, logistic service providers to identify the current situation of the market and provide suggestion for improvement in this sector. Current research confirmed that pure players provide better electronic physical distribution service quality than the multiple channel retailers. Pure players also provide better performance in terms of availability, condition, time and regards which explain this phenomenon. But this raised some issues related to relationships between retailers and logistic service providers. This research is exploratory and it will require further analysis and deeper testing with respect to other contexts and geographical landscapes to assure global validity. The logical parts of the findings give a tactical importance to retailers in empowering competitive advantage and offer exclusive customer service in their segment. The topic eventually continues in putting light on the limited work of physical distribution services. The observations on retailer and logistic service providers point of views relating to the latest research regarding consumer demands and perception of physical distribution service quality is considered